Study of optimizing graphene oxide dispersion and properties of the resulting cement mortars. (10th October 2020) - Yan, Xiantong; Zheng, Dapeng; Yang, Haibin; Cui, Hongzhi; Monasterio, Manuel; Lo, Yiu
Highlights: Sika-PCE is capable of keeping dispersed GO separated even in alkaline environment. The dispersing process has a significant impact on the dispersion of GO. GO can remarkably improve the flexural and compressive strength of cement mortar. SEM and BSE images reveal GO leads to denser matrix and ITZ of cement mortar. Abstract: The effects of both the alkaline environment and calcium ions present in cementitious materials leads to the re-agglomeration of previously dispersed GO, and as a result decreases the dispersion of GO in cement matrix. To solve the aforementioned issues, this study compared 6 different kinds of superplasticizers (SP) to optimize the dispersion of GO in saturated Ca(OH)2 solution which can simulate the strong alkaline environment in the microstructure of cement matrix. And the mechanical properties and microstructures of the resulting cement mortar were investigated systematically. The experimental results present that, among the 6 SPs, Sika-PCE exhibits the best dispersibility with the optimal parameters found to be 30% ultrasonication energy and a SP-to-GO ratio of 1:1. Additionally, the dispersing process was found to have a significant impact on the dispersion of GO. The mechanical properties tests indicate that GO can remarkably improve the flexural and compressive strength of cement mortar in early age. The maximum improvement after 3d curing time was 15.48% for flexural strength with the addition of 0.02 wt% and 14.39% for compressive strength with the addition of 0.04 wt%. Scanning electron microscopy (SEM) and Back scattering images reveal that the incorporation of GO in the cement mortar leads to a denser matrix and stronger interfacial transition zone (ITZ) as compared to plain cement mortar. It can be also found that low GO dosage (0.02 wt%) contributes more to the hydration degree enhancement of the matrix of the cement mortar sample, while higher GO dosage (0.04 wt%) results in a denser ITZ in the cement mortar system. With the GO dosage increasing, energy dispersive X-Ray spectrum (EDS) results demonstrate a strong increasing trend in the Ca/Si ratio in both the interface and matrix regions.